PENGGUNAAN TEPUNG PUCUK INDIGOFERA ZOLLINGERIANA SEBAGAI PENGGANTI BUNGKIL KEDELAI DALAM RANSUM DAN PENGARUHNYA TERHADAP KESEHATAN AYAM BROILER - Melia Afnida Santi (Jurnal Peternakan (Jurnal of Animal Science), 2017)
This research aimed to see the potential ofIndigofera Zollingeriana top leaf meal as substitution of soybean meal in the diets and its effect on the health of broiler chickens. The experiment used 160 day old broiler chicken (Cobb strain). The experimental chicken were provided dietary treatments when they were 15-days old (initial body weight of 460.5±1.56 g/bird) and terminated on day 35. A completely randomized design (CRD) with four treatments and four replications and ten birds in each replication was used in this experiment. Dietary treatments were: R1= diet containing 20% soybean meal without I. zollingeriana top leaf meal ; R2= diet containing 16% soybean meal and 5.9% Indigofera Zollingeriana top leaf meal (substitute 20% soybean meal protein with Indigofera Zollingeriana top leaf meal) ; R3= diet containing 12% soybean meal and 11.8% Indigofera Zollingeriana top leaf meal (substitute 40% soybean meal protein with Indigofera Zollingeriana top leaf meal); R4= diet containing 8% soybean meal and 17.74% Indigofera Zollingeriana top leaf meal (substitute 20% soybean meal protein with Indigofera Zollingeriana top leaf meal).Variable measured was blood profile (red blood cell, hemoglobin, hematocryte, white blood cell, and differensiasi leucocyte). The result showed that usage Indigofera Zollingeriana top leaf meal in the diets did not affect blood profile of broiler chickens. The conclusion of this study wasIndigofera Zollingeriana top leaf meal can be use up to 17.74% to substitute 60% soybean meal protein